Molecular detection and characterization of tick-borne pathogens in dogs and ticks from Nigeria. - Joshua Kamani; Gad Baneth; Kosta Y Mumcuoglu; Ndadilnasiya E Waziri; Osnat Eyal; Yifat Guthmann; Shimon Harrus (Public Library of Science (PLoS), 2013)
BACKGROUND: Only limited information is currently available on the prevalence of vector borne and zoonotic pathogens in dogs and ticks in Nigeria. The aim of this study was to use molecular techniques to detect and characterize vector borne pathogens in dogs and ticks from Nigeria. METHODOLOGY/PRINCIPAL FINDINGS: Blood samples and ticks (Rhipicephalus sanguineus, Rhipicephalus turanicus and Heamaphysalis leachi) collected from 181 dogs from Nigeria were molecularly screened for human and animal vector-borne pathogens by PCR and sequencing. DNA of Hepatozoon canis (41.4%), Ehrlichia canis (12.7%), Rickettsia spp. (8.8%), Babesia rossi (6.6%), Anaplasma platys (6.6%), Babesia vogeli (0.6%) and Theileria sp. (0.6%) was detected in the blood samples. DNA of E. canis (23.7%), H. canis (21.1%), Rickettsia spp. (10.5%), Candidatus Neoehrlichia mikurensis (5.3%) and A. platys (1.9%) was detected in 258 ticks collected from 42 of the 181 dogs. Co- infections with two pathogens were present in 37% of the dogs examined and one dog was co-infected with 3 pathogens. DNA of Rickettsia conorii israelensis was detected in one dog and Rhipicephalus sanguineus tick. DNA of another human pathogen, Candidatus N. mikurensis was detected in Rhipicephalus sanguineus and Heamaphysalis leachi ticks, and is the first description of Candidatus N. mikurensis in Africa. The Theileria sp. DNA detected in a local dog in this study had 98% sequence identity to Theileria ovis from sheep. CONCLUSIONS/SIGNIFICANCE: The results of this study indicate that human and animal pathogens are abundant in dogs and their ticks in Nigeria and portray the potential high risk of human exposure to infection with these agents.